Industrialization and the return to labor: Evidence from Prussia - Ann-Kristin Becker; Erik Hornung (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2025)
Industrialization boosts aggregate incomes, but its distributional effects remain debated. We study the impact of coal-driven industrialization on unskilled labor incomes using novel panel data on wages from 667 Prussian localities (1800-1879), extended with county-level data through 1914. Exploiting spatial variation in coal proximity in difference-in-differences and event-study designs, we find that wage gains in coal-rich regions emerged once industrialization accelerated in the 1850s and continued to grow until WWI. Evidence from 3,000 household accounts shows that coal proximity raised labor incomes primarily for low-skilled workers, with weaker effects for high-skilled and mechanical occupations. This pattern suggests that industrialization reduced wage inequality by compressing the local skill premium. Mediation analysis indicates that wage gains for unskilled workers were primarily driven by technology adoption and the increasing demand for low-skilled labor, rather than by sectoral change or the spread of the factory system.
Keywords: C23; J31; N33; N73; N93; O13; 330; Industrialization; Labor income; Energy transition; Structural change; Technological change; Deskilling; Nineteenth-century Prussia